GUIDELINES FOR INCREASING MANAGEMENT EFFICIENCY OF COMMUNITY ENTERPRISES IN MUANG DISTRICT, NAKHON SAWAN PROVINCE - Tharathueke, Boonsan; Klongkarnying, Apichij; Kaenkaew, Thanunchai (Journal of MCU Nakhondhat, 2024)
The objectives of this study were 1) Guidelines to increase the management efficiency of community enterprises in Mueang District, Nakhon Sawan Province and 2) To compare the approaches to increase the management efficiency of community enterprises in Mueang District, Nakhon Sawan Province. This research is a quantitative research method. The sample group was 400 members of community enterprises in Mueang District, Nakhon Sawan Province, and the statistics were analyzed with frequency, percentage, mean, and standard deviation, and inverential statistics. The results of the study showed that most of the members of community enterprises were women aged 41 - 50 years old. Agricultural occupation Have an average income of 10,000 - 20,000 baht, have been a member of a community enterprise for more than 4 years. The average is moderate. In terms of finance, followed by production, management, and marketing. The results of the test hypothesis that the sample were male and female had an effect on the optimization of marketing management. (P-value < 0.05) for the sample with different levels of education had an effect on the optimization of marketing management. (p-value < 0.05) for the sample with different occupational groups had an effect on the efficiency of management. Marketing the sample with different incomes had an effect on the efficiency of financial and administrative management (p-value < 0.05) and the members of community enterprises with different membership periods had an effect on the efficiency of management management (p-value < 0.05).